2015
DOI: 10.1038/ncomms8168
|View full text |Cite
|
Sign up to set email alerts
|

Trans-synaptic zinc mobilization improves social interaction in two mouse models of autism through NMDAR activation

Abstract: Genetic aspects of autism spectrum disorders (ASDs) have recently been extensively explored, but environmental influences that affect ASDs have received considerably less attention. Zinc (Zn) is a nutritional factor implicated in ASDs, but evidence for a strong association and linking mechanism is largely lacking. Here we report that trans-synaptic Zn mobilization rapidly rescues social interaction in two independent mouse models of ASD. In mice lacking Shank2, an excitatory postsynaptic scaffolding protein, p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
104
2
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(109 citation statements)
references
References 70 publications
2
104
2
1
Order By: Relevance
“…They often interact with tetraspanins and appear to mediate many cellular outcomes [50, 56]. Moreover, ECM-integrin interactions also play major roles in EV binding and uptake by cells [10, 21, 36, 49, 57, 58] (Figure 2A). Thus, inhibiting fibronectin on the surfaces of MDAMB231-derived MVs from binding or activating α 5 β 1 integrins on recipient fibroblasts, by treating the cells with the RGD peptide (a peptide that blocks fibronectin-integrin interactions), inhibited the MVs from inducing the anchorage-independent growth of fibroblasts [10].…”
Section: Ev Targeting and Docking On Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…They often interact with tetraspanins and appear to mediate many cellular outcomes [50, 56]. Moreover, ECM-integrin interactions also play major roles in EV binding and uptake by cells [10, 21, 36, 49, 57, 58] (Figure 2A). Thus, inhibiting fibronectin on the surfaces of MDAMB231-derived MVs from binding or activating α 5 β 1 integrins on recipient fibroblasts, by treating the cells with the RGD peptide (a peptide that blocks fibronectin-integrin interactions), inhibited the MVs from inducing the anchorage-independent growth of fibroblasts [10].…”
Section: Ev Targeting and Docking On Cellsmentioning
confidence: 99%
“…In the context of cancer, EVs have been extensively studied and shown to promote a wide range of processes that underlie cancer progression, including inflammatory responses [5], angiogenesis [2, 31-33], metastasis [34, 35], cell migration [36], proliferation [10, 37, 38], and immune suppression [39, 40] (Figure 1A). One study demonstrating the potential effects of EVs on cancer progression showed that EVs from cancer cells can affect normal cells that are adjacent to tumors.…”
Section: Introductionmentioning
confidence: 99%
“…The list of mutations associated with ASDs and the number of mouse models is growing rapidly, yet understanding the connection between genetic mutation, synaptic defects, and disease phenotypes remains a challenge. Mutations in SHANK genes occur in autistic patients (Durand et al, 2007;Berkel et al, 2010;Sato et al, 2012) and Shank mutant mice reproduce several autism-related phenotypes (Bozdagi et al, 2010;Peça et al, 2011;Wang et al, 2011;Schmeisser et al, 2012;Won et al, 2012;Lee et al, 2015;Peter et al, 2016). SHANKs (short for SH3 and multiple ankyrin repeat domains protein, also referred to as ProSAPs) are scaffold proteins in the postsynaptic density of mammalian excitatory synapses that interact with numerous synaptic proteins (Monteiro and Feng, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…SHANKs (short for SH3 and multiple ankyrin repeat domains protein, also referred to as ProSAPs) are scaffold proteins in the postsynaptic density of mammalian excitatory synapses that interact with numerous synaptic proteins (Monteiro and Feng, 2017). Recent reports have made a strong case for NMDA receptor hypofunction and/or defective long-term potentiation as a cause for disease-relevant behavioural phenotypes in Shank2 and Shank3 mutant mice (Won et al, 2012;Lee et al, 2015;Peter et al, 2016) and Shank3 (Bozdagi et al, 2010;Peça et al, 2011;Kouser et al, 2013) and it has even been suggested that pharmacological upregulation of LTP can be used to reverse the phenotype (Won et al, 2012;Bozdagi, Tavassoli and Buxbaum, 2013). In sharp contrast to all other studies on the function of SHANK proteins we observe an enhancement of synaptic plasticity in Shank2 -/mice (Schmeisser et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…4c inset), indicating that hearing per se was not impaired but the reaction to stimulus is altered. Because NMDAR mutations are associated with autism spectrum disorder (ASD, (Hacohen et al, 2016;Grea et al, 2017;Rossi et al, 2017) and repetitive behavior in mice (Lee et al, 2015;Kim et al, 2019), we evaluated additional ASD-relevant behaviors using established criteria in rodents. Although S644G/+ mice showed no impairments in the same-sex reciprocal social interaction test (Supplementary Fig.…”
Section: A De Novo Grin2a Variant In a Child With Deementioning
confidence: 99%